2011
DOI: 10.1371/journal.pone.0016154
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal Perceptual Aberrations of Time: Correlation between Score, Behavior and Brain Activity

Abstract: A fundamental trait of the human self is its continuum experience of space and time. Perceptual aberrations of this spatial and temporal continuity is a major characteristic of schizophrenia spectrum disturbances – including schizophrenia, schizotypal personality disorder and schizotypy. We have previously found the classical Perceptual Aberration Scale (PAS) scores, related to body and space, to be positively correlated with both behavior and temporo-parietal activation in healthy participants performing a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
(137 reference statements)
2
12
0
Order By: Relevance
“…As expected, individuals with schizophrenia had on average larger temporal binding windows and required larger temporal differences before they could reliably detect an asynchrony between a visual and tactile stimulus. This is consistent with well-documented perceptual changes in the temporal domain in schizophrenia (Arzy, Mohr, Molnar-Szakacs, & Blanke, 2011;Foucher et al, 2007;Stevenson et al, 2017). It is important to note that, although the group level effects are robust, the data plots show that not all individuals diagnosed with schizophrenia have increased asynchrony detection thresholds compared to the control group mean.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, individuals with schizophrenia had on average larger temporal binding windows and required larger temporal differences before they could reliably detect an asynchrony between a visual and tactile stimulus. This is consistent with well-documented perceptual changes in the temporal domain in schizophrenia (Arzy, Mohr, Molnar-Szakacs, & Blanke, 2011;Foucher et al, 2007;Stevenson et al, 2017). It is important to note that, although the group level effects are robust, the data plots show that not all individuals diagnosed with schizophrenia have increased asynchrony detection thresholds compared to the control group mean.…”
Section: Discussionsupporting
confidence: 90%
“…Meehl (1990), in his theory of schizophrenia and schizotypy, suggests that spatial-kinesthetic-vestibular system aberrations could account for bodily aberrations. Interestingly, previous neurophysiology research using electroencephalography (EEG) recordings found that bodily perceptual aberration (in participants without a schizophrenia diagnosis) was positively correlated with the duration but not the strength of activation of temporal-parietal cortex during a body transformation task (Arzy, Mohr, Michel, & Blanke, 2007;Arzy et al, 2011). This change in duration of neural activity suggests that temporal processing changes also influence the integration of visual, somatosensory with vestibular inputs and provides further indirect evidence for the role of temporal processing for aberrant spatial body perception.…”
Section: Discussionmentioning
confidence: 91%
“…Susceptibility was assessed with the 20-item time Perceptual Aberration Scale (tPAS) and identified no individuals scoring within the top 10% of the scale. Past research found a strong correlation between the tPAS and the Perceptual Aberration Scale (i.e., measuring vulnerability to schizophrenia spectrum disorders), and between high tPAS scores and right angular gyrus (AG) dysfunction 38 . See Table S1 for a full list of exclusion criteria.…”
Section: Participants Thirty-six Naive Right-handed Adults With Normmentioning
confidence: 99%
“…Finally, hyperactivity, as defined here, is based on prolonged duration of the corresponding topographical EEG map. Map-duration was found previously to characterize pathological neuropsychiatric states [19].…”
Section: Discussionmentioning
confidence: 89%
“…These epochs were subjected to topographic analysis in the frequency domain using Fast-Fourier-Transform (FFT) applied on conventional frequency bands of delta (1-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), low beta (13-18 Hz), medium beta (18-24 Hz), high-beta (24-30 Hz) lowgamma (30-40 Hz) mid-gamma (40-55 Hz) and high-gamma (55-70 Hz). After applying the bandpass filter to the different frequency bands, the analyzed multichannel data were transformed into topographic maps, also termed "microstates" [19,20]. For each frequency band, 10 different microstates were found across the two phases using a k-means clustering approach [21].…”
Section: Methodsmentioning
confidence: 99%